Starting the Indigenisation Process of Social Work Practice in Malaysia - Adam Andani Mohammed; MD Sayed Uddin; Bassoumah Bougangue (Social Work and Society, 2020)
This study focuses on the extent to which social work practice in Malaysia can be indigenised. The social work programmes and practices needs to accommodate the traditions and sociocultural practices of the people to provide adequate and relevant services. Considering the shortcomings and inadequacies of current social work theories and practices, social problems in Malaysia might better be handled if the practice of social work is indigenised. Combination of direct and summative qualitative content analysis research methods is adopted. As such, the studies assessed factors encouraging social work practice and why the need to indigenise social work in Malaysia. To get relevant data, Google Scholar was used as a tool to access the major databases provided by Tailor and Frances, Emerald, Elsevier, Springer, Sage and others. Relevant literature reveals that for development with indigenisation, social workers have delved into different forms of service delivery and different assumptions as proposed service delivery in other parts of the globe.  It is revealed that the analysis of social workers is centered at the micro level due to the casework orientation.